PENERAPAN STANDARISASI PENGELOLAAN PAUD (PENDIDIKAN ANAK USIA DINI) DI TK LABORATORIUM FKIP UNIVERSITAS RIAU PEKANBARU - Anggi Saputri Bama; Dr Daviq Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: The background of this research because the where the research has not met the standards as in Permendiknas. The purpose of this study was to determine the Application of Standards in kindergarten early childhood Management Laboratory FKIP Riau University. This type of research is qualitative research used to examine the natural conditions, where the researcher is a key instrument, sampling data sources. Which is the object of this research is the manager of TK Laboratory FKIP Pekanbaru Riau University. Data collection is done by; interview, observation and documentation study. the study was conducted during the month, interviewed the manager TK, objectives of management / general management of early childhood education is the key word for covers effective and efficient, so it is intended that the management of early childhood education goals as planned effectively and efficiently. As for out of 5 things: planning, organizing, supervision, implementation, and assessment. Keywords: standardization, management, early childhood education